ANALISIS PEMASARAN KELAPA DALAM DI DESA MELI KECAMATAN BALAESANG KABUPATEN DONGGALA - Firdayanti Firdayanti; Abdul Muis; Hendra Pribadi (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2022)
The objective of this study is to identify the type of marketing channels, marketing margins, the proportion of the price given to farmers, and the effectiveness of marketing coconut in Meli village, Balaesang sub district, Donggala district, which was conducted between January and March 2022. A total of 33 farmers were chosen randomly from a population of 125 farmers, and the sample of traders was determined using the snowball method, which resulted in 2 collectors and 1 wholesaler, for a total of 36 respondents. The research revealed that there are two marketing channels in Meli Village: Channel I (farmers - collectors - wholesalers - consumers) with a margin of IDR 1,300/kg and a farmer's share of 60.6%, and Channel II (farmers - wholesalers - consumers) with a margin of IDR 700/kg and a farmer's share of 78.8%. The marketing efficiency of Channel I is 30.88%, and that of Channel II is 28.64%. Overall, Channel II is more efficient than Channel I, as it has a smaller margin, a larger price share for farmers, and a lower efficiency value. Therefore, the short marketing channel is more efficient than the long channel.